Visible light photo response from N-doped anodic niobium oxide after annealing in ammonia atmosphere - Ruff, T.; Hahn, Robert; Killian, M. S.; Asoh, H.; Ono, S.; Schmuki, Patrik (Electrochimica Acta, 2012)
Niobium oxide films with a thickness of approximately 165 nm were prepared by electrochemical anodization. These anodic oxide layers were then treated in an ammonia atmosphere at different temperatures and durations, and characterized with XRD, XPS, ToF-SIMS and photoelectrochemical methods. Under optimized conditions nitrogen doping of the niobium oxide films takes place, resulting in a distinct photo response in the visible range of light.
EAM Import::2019-03-13